Valor económico del volumen de madera de las especies forestales comerciales de un bosque natural de colina baja de la cuencua del río Cochiquinas, Pebas. Loreto, 2017 - Ramírez López, Antony Javier (2018)
The objective of this study was to economically valuate the commercial species of a slightly uneven low-hill natural forest (BCbl) located in the Cochiquinas river basin, district of Pebas, province of Mariscal Ramón Castilla, Loreto; Peru. All tree indivduals with BDH?MCD of commercial forest especies included in PC 01 of 251,20 ha , belonging to the forest concession 16-LOR-MAR/COM-MAD-2016-049, were recorded and then determined the floristic composition and the volume of standing lumber. A total of 288 tree individuals included in nine forest species and seven botanical families were recorded, representing a density of 1,15 ind/ha, Myristicaceae is the most representative family with two forest species: O. glycicarpa and V. caducifolia, with a total of 121 registered tree individuals. O. glycicarpa contains the highest number of individuals of 0,28 ind/ha and C. pentandra the lowest number of 0,02 ind/ha. C. cateniformis, O. glycicarpa and P. igneiflora are the species with the highest ecological weight (IVI= 186,77), while A. panurensis, C procera, C. pentandra and C. longifolium are the ones with the least ecological importance (55,41%). This type of forest contains a commercial timber volume of 5,86 m3/ha, valuated at S/. 100 545,16 ($31 225,20)